Integrating Technology in Teaching and Learning Mathematics - Paulina Pannen (Southeast Asian Mathematics Education Journal, 2015)
With the rapid development of ICT and its ramification in our world, especially education, can we envision how education will look like in the future, especially in Indonesia, and in the teaching and learning of mathematics? Employing Zappa’s Envisioning the Future of Educational Technology (2013) and NMC Horizon Report (2014) K-12 Edition, this paper will reflect on the effort of ICT integration in teaching and learning, especially in the teaching and learning of mathematics, in Indonesia. Taking stock of the existing Government’s policy on ICT and ICT in Education, also of the facts and figures of Indonesia’s ICT profile, this paper discusses initiatives, practices, and studies of ICT in Education, integration of ICT in the teaching and learning of mathematics, what technology and how to integrate in the teaching and learning of mathematics, and some future prediction on the evolution of teaching and learning due to emerging technologies.